Comparative analysis of cryogenic distillation and chemical absorption for carbon capture in integrated natural gas liquefaction processes. (10th January 2023) - He, Ting; Liu, Zhongxuan; Son, Heechang; Gundersen, Truls; Lin, Wensheng
Abstract: Compared with the widely used chemical absorption, cryogenic distillation has a lower thermal energy consumption and smaller footprint of the carbon capture unit. However, the power consumption of cryogenic distillation is higher. This study aims to use the azeotropic properties of ethane-CO2 mixtures to achieve CO2 capture by cryogenic distillation for cleaner LNG production. A single mixed refrigerant LNG process integrated with cryogenic distillation (CD-LNG) or chemical absorption (CA-LNG) is proposed. These technologies are comprehensively compared with respect to energy, economy and environment. The results show that when the feed gas contains 1.8–17 mol% CO2, the power consumption of the CA-LNG process is 0.37–0.40 kWh/Nm 3 NG with an exergy destruction of 0.20–0.23 kWh/Nm 3 NG. The power consumption of the CD-LNG process is 0.41–0.42 kWh/Nm 3 NG with an exergy destruction of 0.18–0.22 kWh/Nm 3 NG. Due to the much higher heat load for chemical solvent regeneration, the overall exergy efficiency of the CA-LNG process (49.0–53.8%) is lower than that of the CD-LNG process (50.6–56.0%). In addition, the total annualized cost (TAC) in a 20-years lifespan of the CD-LNG and the CA-LNG for a case study with a process scale of 179, 800 t/a and a specified feed gas composition (79 mol% CH4, 10 mol% C2 H6 and 11 mol% CO2 ) are 8, 441, 117 $ and 9, 860, 792 $ respectively. The GWP analysis shows that the CO2 -eq of the CA-LNG process is 37–67% higher than that of the CD-LNG process. Highlights: CO2 capture by absorption and distillation is integrated with LNG production. The exergy efficiency of chemical absorption system (CA-LNG) is 49.0–53.8%. The exergy efficiency of cryogenic distillation system (CD-LNG) is 50.6–56.0%. The total annualized costs of CA-LNG are 16.8% higher than that of CD-LNG. The GWPs of CD-LNG and CA-LNG are analyzed in a lifespan of 20 years.